Adaptasi tanaman padi terhadap stress - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
An experiment about the adaption of rice were planted to MURASHIGE and SKOOG medium supplemented with sea water consentration of 17,5%